NUTRITIONAL AND ZOOTECHNICAL ASPECTS OF NIGELLA SATIVA:A REVIEW - E. Longato; G. Meineri; P.G. Peiretti (Journal of Animal and Plant Sciences, 2015)
This review outlines the knowledge on the nutritional and zootechnical aspects of Nigella sativa (NS),which is an annual herbaceous plant native to Turkey, Pakistan and Iran. The popularity of this plant is due to its beneficial actions. NS is considered one of the most important medicinal plants in the world. Itsseeds have many therapeutic effects, including antimicrobial, anticoccidial and anthelminthic activities, most of which are due to the presence of thymoquinone, which is the major bioactive component. NS seeds are also a significant source of proteins, carbohydrates and fatty acids, and thus could be added as an ingredient to formulate balance rations for farm animals. NS had positive effects on productive and reproductive performances, mortality rate, digestibility, blood chemistry parameters, milk yield and composition, compositional characteristics of eggs and carcass traits.
Keywords: Nigella sativa; Digestibility; Intake; Nutritive value; Growth performance; Health status